Spatial distribution, Leishmania species and clinical traits of Cutaneous Leishmaniasis cases in the Colombian army (2017)
In Colombia, the cutaneous leishmaniasis (CL) is the most common manifestation across the army personnel. Hence, it is mandatory to determine the species associated with the disease as well as the association with the clinical traits. A total of 273 samples of male patients with CL were included in the study and clinical data of the patients was studied. PCR and sequencing analyses (Cytb and HSP70 genes) was performed to identify the species and the intra-specific genetic variability. A georeferenced database was constructed to identify the spatial distribution of Leishmania species isolated. The identification of five species of Leishmania that circulate in the areas where army personnel are deployed is described. Predominant infecting Leishmania species corresponds to L. braziliensis (61.1%), followed by Leishmania panamensis (33.5%), with a high distribution of both species at geographical and municipal level. The species L. guyanensis, L. mexicana and L. lainsoni were also detected at lower frequency. We also showed the identification of different genotypes within L. braziliensis and L. panamensis. In conclusion, we identified the Leishmania species circulating in the areas where Colombian army personnel are deployed, as well as the high intra-specific genetic variability of L. braziliensis and L. panamensis and how these genotypes are distributed at the geographic level. © 2017 Patino et al.